Effect of Computer Efficacy Training in the Management of Computer Anxiety among National Open University of Nigeria Freshmen - David Adebayo Oluwole; Joseph Babajide Oyadeyi (West African Journal of Open and Flexible Learning)
Computer anxiety has been identified as a prominent drawback to many freshmen in the Open and Distance Learning (ODL) institutions in Nigeria. It is a known fact that inadequate computer skills coupled with computer anxiety are linked to attrition rate and poor academic performance among distance learners who by exigency should utilise computer to bridge the transactional and interactional distance that exist between them, their tutors and other relevant personnel. This study, therefore, determined the effectiveness of Computer Efficacy Training (CET) in the management of computer anxiety among National Open University of Nigeria (NOUN) freshmen in Southwestern Nigeria. The moderating effects of age and gender were examined.